Predicting and testing a gene network regulating seed germination in Arabidopsis - Ming Yang; Yixing Wang (PeerJ)
Maternal auxin signaling inhibits seed germination in Arabidopsis, but little is known about the gene network that mediates the inhibition of seed germination by auxin. Based on publicly available data, we first determined the expression patterns of AUXIN SIGNALING F-BOX (AFB) genes in the funiculus (FUN)-chalazal seed coat (CSC) continuum. We found that TIR1, AFB1, and AFB4 exhibited a down-expression gradient and AFB2, AFB3, and AFB5 an up-expression gradient from FUN to CSC, and members in each of the two AFB groups were linearly correlated in expression in FUN, CSC, and the distal seed coat (DSC). We then searched for auxin-regulated genes that exhibited one of the two expression gradients. We found 118 such genes that were assigned into four groups based on their response mode to auxin and expression gradient direction. The four groups were further broken down into 12 subgroups based on the linear correlation coefficient values. Only three of the 12 subgroups, including a total of 30 genes with 21 of them being known or highly likely to function in the seed germination process. To explore whether additional genes of the remaining nine play roles in seed germination, we tested mutants of five of them in a germination assay and found all of them exhibited either delayed or hastened germination. The experimental results support the validity of our approach for predicting the involvement of these genes in seed germination. Based on publicly available data and data from this investigation, we constructed a gene network, which should provide a valuable framework and new clues for future studies of the molecular mechanism controlling seed germination.